"Create Your Own Business": Sociological Analysis of the Entrepreneurial Actions - ФидряЕфим Сергеевич (Journal of Economic Sociology, 2010)
The goal of the research was to study the social embeddedness of the entrepreneurial action on the basis of the analysis of the strategy for opening your own business. This issue is analyzed on the example of the private hospital in Magadan. The author makes the conclusion that social factors influence the formation of the entrepreneurial orientation. They are social-economic context, cultural norms, values, that were worked out before the entrepreneurial period and that defined the entrepreneurial action. Organizing your own business is the adaptive strategy that let us to implement valuable personal goals but at the same time the choice of this particular way is not casual and determined by the personal characteristics formed during the period of the initial socialization.